The Influence of Fundamental Macroeconomic Performance and Corporate Actions In Indonesia on Stock Prices - Ingga Maulana; Achmad Khusnul Iman (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
The capital market is a key pillar of the financial system that reflects a country’s economic conditions. Stock price movements, particularly in the banking sector, are influenced by macroeconomic factors such as interest rates and exchange rates, as well as corporate actions like dividend payout ratios. This study aims to examine the effects of interest rates, exchange rates, dividend payout ratios, and firm size on banking stock prices listed on the Indonesia Stock Exchange, both partially and simultaneously. The study employs a quantitative approach using secondary data from 28 banking companies during 2023. Panel data regression analysis is applied using E-Views 12, including descriptive statistics, classical assumption tests, and model selection among pooled least squares, fixed effects, and random effects models. The expected outcomes include publication in an accredited national journal and policy recommendations for the Financial Services Authority and Bank Indonesia. The study contributes to the literature on capital markets and provides practical insights for banking management and investors in making data-driven decisions